RANCANG BANGUN SISTEM INFORMASI E-ARSIP BERBASIS MICROSOFT ACCESS DALAM PENANGANAN ARSIP INAKTIF (STORING, PLACING, FINDING) DI DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KOTA MALANG - Sovia Rosalin; Mochamad Ariiq Hendrawanto (Program Pendidikan Vokasi Universitas Brawijaya, 2020)
Abstract : Design of E-Archive Information Systems Based on Microsoft Access Handling Inactive Records (Storing, Placing, Finding) in Public Works and Spatial Planning Office of Malang City. Every implementation of activities in an institution or agency will always produce an archive that is created. The more activities that are carried out the more archives are created, ranging from active dynamic records, inactive dynamic records, to static records. The type of archive that is rarely used anymore for the purposes of carrying out administrative activities is the type of inactive dynamic archive. Malang City DPUPR has established an archive space as a storage area that can manage and store dynamic inactive records. But in managing the archive space is still constrained by the maximum storage, placement, and retrieval of archives. This final project aims to design and build an e-archive information system based on Microsoft Access in handling inactive records in the Public Works and Spatial Planning Office in Malang. Inactive archive data used is the type of KRK archive (Description of City Plan) in 2016. The final project method used is Waterfall which includes stages: requirements (requirements analysis), system design, Coding and Testing, program implementation, maintenance. The result of this final project is the design of application programs and applications that have been built can be used as an alternative media for handling electronic records in Malang City DPUPR with the benefits of speed, ease and accuracy.